2014
DOI: 10.1016/j.jmmm.2014.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non-magnetic and magnetic ions on the MagnetoCaloric properties of La0.7Sr0.3Mn0.9M0.1O3 doped in the Mn sites by M=Cr, Sn, Ti

Abstract: International audienceWe have studied the MagnetoCaloric Effect (MCE) in La0.7Sr0.3Mn0.9M0.1O3, M=Cr, Sn and Ti, prepared by a conventional solid state reaction. The temperature dependence of magnetization reveals that all compositions exhibit a ferromagnetic (FM) to paramagnetic (PM) transition at TC temperatures of 369, 326, 228 and 210 K, respectively for La0.7Sr0.3MnO3 (LSMO), La0.7Sr0.3Mn0.9Cr0.1O3 (LSMO-Cr), La0.7Sr0.3Mn0.9Sn0.1O3 (LSMO-Sn), and La0.7Sr0.3Mn0.9Ti0.1O3 (LSMO-Ti). Using Arrott plots, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(20 citation statements)
references
References 58 publications
(57 reference statements)
3
17
0
Order By: Relevance
“…The largest -∆S M occurs near T C , which is a property of simple ferromagnets due to the efficient ordering of magnetic moments induced by the magnetic field at T C . 29 The maximum magnetic entropy changes observed for x=0, x=0.02, x=0.07, and 0.1 compositions are 0.85, 0.77, 0.63, and 0.59 J/kg K at 1.5 T. The value of -∆S M for the undoped sample is in good agreement with that reported in Ref. 9, in which LCMO particles with mean diameters of ∼15 nm were synthesized by sol-gel method.…”
Section: Resultssupporting
confidence: 89%
“…The largest -∆S M occurs near T C , which is a property of simple ferromagnets due to the efficient ordering of magnetic moments induced by the magnetic field at T C . 29 The maximum magnetic entropy changes observed for x=0, x=0.02, x=0.07, and 0.1 compositions are 0.85, 0.77, 0.63, and 0.59 J/kg K at 1.5 T. The value of -∆S M for the undoped sample is in good agreement with that reported in Ref. 9, in which LCMO particles with mean diameters of ∼15 nm were synthesized by sol-gel method.…”
Section: Resultssupporting
confidence: 89%
“…Figure 3(b) shows the dependence of RCP on applied field H. Clearly, the RCP increased with H and under applied field of ΔH = 50 kOe, its value is 250 J/kg. This value is large than those of La0.67Sr0.33Mn0.9M0.1O3 with M = Cr, Sn, Ti [23] and La0.67Ba0.33MnO3 [24]. Within the framework of second order phase, the field dependence of the magnetic entropy change follows a power law of the filed ΔSm α H n with an exponent, n, which depends on temperature and field.…”
Section: Resultsmentioning
confidence: 86%
“…The T c of La x M 1‐ x ‐ z R z Mn y N 1‐ y O 3 perovskite can be adjusted by designing its composition. Studies have shown that many applications of La x M 1‐ x ‐ z R z Mn y N 1‐ y O 3 perovskites, such as magnetic cooling, magneto‐dependent sensor, and magnetism storage, are closely related to the T c . Therefore, accurate prediction of T c is a very rewarding job in materials design.…”
Section: Case Studiesmentioning
confidence: 99%
“…The dataset consisted of 35 compounds of La x M 1‐ x ‐ z R z Mn y N 1‐ y O 3 perovskites with known T c between 160 and 369 K, which was collected from 20 references . The candidate descriptors were proposed based on the domain knowledge of perovskite compounds.…”
Section: Case Studiesmentioning
confidence: 99%